2003
DOI: 10.1002/humu.10226
|View full text |Cite
|
Sign up to set email alerts
|

Clear relationship betweenETF/ETFDH genotype and phenotype in patients with multiple acyl-CoA dehydrogenation deficiency

Abstract: Mutations in electron transfer flavoprotein (ETF) and its dehydrogenase (ETFDH) are the molecular basis of multiple acyl-CoA dehydrogenation deficiency (MADD), an autosomal recessively inherited and clinically heterogeneous disease that has been divided into three clinical forms: a neonatal-onset form with congenital anomalies (type I), a neonatal-onset form without congenital anomalies (type II), and a late-onset form (type III). To examine whether these different clinical forms could be explained by differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
178
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(190 citation statements)
references
References 38 publications
(43 reference statements)
9
178
0
3
Order By: Relevance
“…The mutation identified in this study has not been reported previously in human cases of MADD (Goodman et al 2002;Olsen et al 2003;Schiff et al 2006;Yotsumoto Er et al 2010;Wolfe et al 2010;Er et al 2011;Wang et al 2011;Trakadis et al 2012) (Fig. 5c).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The mutation identified in this study has not been reported previously in human cases of MADD (Goodman et al 2002;Olsen et al 2003;Schiff et al 2006;Yotsumoto Er et al 2010;Wolfe et al 2010;Er et al 2011;Wang et al 2011;Trakadis et al 2012) (Fig. 5c).…”
Section: Discussionsupporting
confidence: 49%
“…4b). In humans, most cases of MADD are attributable to a zygotic effect on different mutations in ETF or ETFDH (Olsen et al 2003), although the majority of patients with late-onset MADD recorded in southern China carried a homozygous mutation of c.250G>A in ETFDH (Wang et al 2011). According to the owner, the present cat is derived from a group of dozens of stray cats, which were fed by a particular person.…”
Section: Discussionmentioning
confidence: 99%
“…ETF is a dimeric mitochondrial matrix protein composed of ␣ -and ␤ -subunits, and a mutation in either subunit or in ETFDH will result in MADD ( 213 ). Null mutations in either ETFB or ETFDH appear to be associated with the neonatal onset (type 1) of the disease ( 213,214 ). Its mode of inheritance follows an autosomal-recessive pattern.…”
Section: Familial Hypertrophic Cardiomyopathy and Inherited Dilated Cmentioning
confidence: 99%
“…The severity and age at onset of MADD is speculated to correlate with the genotype and residual enzyme activity. Olsen et al described that the clinical phenotype can be explained by ETF/ETFDH genotype that results in different levels of residual enzyme activity (13). That is, null mutations, which would not be expected to result in any residual ETF/ETFDH enzyme activity, result in the development of congenital anomalies and thereby type 1, and even small amounts of residual activity is sufficient to give rise to the type 2 phenotype.…”
Section: Table 2 Serum Ck Acylcarnitine and Urine Organic Acid Befmentioning
confidence: 99%
“…That is, null mutations, which would not be expected to result in any residual ETF/ETFDH enzyme activity, result in the development of congenital anomalies and thereby type 1, and even small amounts of residual activity is sufficient to give rise to the type 2 phenotype. And the type 3 phenotype is caused by at least one allele with a single missense mutation, which is not directly involved in the active site and has no apparent effect on mRNA processing or stability, and shows significant residual enzyme activity (13). In the Japanese population, though some missense mutations have been reported to be associated with the mild/late onset form (14), no obvious clustering of mutations has been established.…”
Section: Table 2 Serum Ck Acylcarnitine and Urine Organic Acid Befmentioning
confidence: 99%